Molecular characterization of group A bovine rotavirus in southeastern and central-western Brazil, 2009-2010 - Silva, Fernanda D.F. [UNESP]; Gregori, Fábio; Gonçalves, Ana C. S. [UNESP]; Samara, Samir Issa [UNESP]; Buzinaro, Maria G. [UNESP] (Colégio Brasileiro de Patologia Animal - CBPA, 2012)
Rotavírus é uma importante causa de diarreia neonatal em humanos e várias espécies animais, incluindo bezerros. Foi realizado um estudo a partir de 792 amostras fecais colhidas de bezerros, provenientes de 65 rebanhos de leite e corte distribuídos em duas das maiores regiões produtoras no Brasil, com o objetivo de se detectar a ocorrência de rotavírus e realizar a sua caracterização molecular quanto aos genotipos G e P nestas regiões. Um total de 40 (5,05%) de amostras testadas foram positivas para rotavírus pela técnica de eletroforese em gel de poliacrilamida (PAGE). A caracterização molecular foi realizada através de reações do tipo Multiplex semi-nested RT-PCR demonstrando que as associações de genotipos circulantes em rebanhos da região Sudeste foram G6P[11], G10[P11], G[-]P[5]+[11], G[-]P[6] no Estado de São Paulo e G6P[11], G8P[5], G11P[11], G10P[11] no Estado de Minas Gerais. Na região Centro-Oeste, foram detectados no Estado de Goiás os genotipos G6P[5]+[11], G6P[5], G8P[-], G6P[11], G[-]P[1], G[-]P[11], G[-]P[5] enquanto os genotipos G6P[5], G8[P11], G6[P11], G8[P1], G8[P5], G6[P1] eram circulantes em rebanhos do Estado do Mato Grosso do Sul. A diversidade genotípica de rotavírus bovino encontrada em cada região estudada justifica a importância da caracterização das amostras circulantes para medidas profiláticas mais efetivas.

Rotavirus is an important cause of neonatal diarrhea in humans and several animal species, including calves. A study was conducted to examine 792 fecal samples collected from calves among 65 dairy and beef herds distributed in two of Brazil's major livestock producing regions, aiming to detect the occurrence of rotavirus and perform a molecular characterization of the rotavirus according to G and P genotypes in these regions. A total of 40 (5.05%) samples tested positive for rotavirus by the polyacrylamide gel electrophoresis (PAGE) technique. The molecular characterization was performed by multiplex semi-nested RT-PCR reactions, which indicated that the associations of genotypes circulating in herds in Brazil's southeastern region were G6P[11], G10P[11], G[-]P[5] + [11], G[-]P[6] in the state of São Paulo and G6P[11], G8P[5], G11P[11], G10P[11] in the state of Minas Gerais. In the central-western region, the genotypes G6P[5] + [11], G6P[5], G8P[-], G6P[11], G [-] P[1], G[-] P[11], and G[-] P[5] were detected in the state of Goiás, while the genotypes G6P[5], G8[P11], G6[P11], G8[P1], G8[P5], G6[P1] were circulating in herds in the state of Mato Grosso do Sul. The genotypic diversity of bovine rotavirus found in each region under study underlines the importance of characterizing the circulating samples in order to devise the most effective prophylactic measures.
Caracterização molecular de rotavírus bovino do grupo A nas regiões Sudeste e Centro-Oeste do Brasil
Keywords: Rotavirus; Diarrhea; Genotypes; Cattle; Brazil; Rotavírus; Diarréia; Genótipos; Bovino; Brasil